The public good in English private school governance. (November 2015) - Boyask, Ruth
There exist some rare private schools that attempt to mitigate the anti-democratic qualities of the private schooling sector in England. This article reports on a study of private schools that aim to promote equality and participation through some aspects of their operations. It considers to what extent the governance structures within the schools support their aspirations and what this means for the public good more generally. English private schools are accountable to the state under The Education (Independent School Standards) Regulations 2014 (hereafter Independent School Standards, 2014), corporate law and the majority are accountable under the Charities Act, which requires them to demonstrate public benefit. The schools reported here have a commitment to the public good that extends beyond these limited accountabilities, demonstrating the weaknesses of the public good as it is presently defined by the state and also advancing understanding on the extent to which the schools can be regarded as Fraser's (1990) counterpublics.